9(e-1)=-7e-9

Simple and best practice solution for 9(e-1)=-7e-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(e-1)=-7e-9 equation:


Simplifying
9(e + -1) = -7e + -9

Reorder the terms:
9(-1 + e) = -7e + -9
(-1 * 9 + e * 9) = -7e + -9
(-9 + 9e) = -7e + -9

Reorder the terms:
-9 + 9e = -9 + -7e

Add '9' to each side of the equation.
-9 + 9 + 9e = -9 + 9 + -7e

Combine like terms: -9 + 9 = 0
0 + 9e = -9 + 9 + -7e
9e = -9 + 9 + -7e

Combine like terms: -9 + 9 = 0
9e = 0 + -7e
9e = -7e

Solving
9e = -7e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '7e' to each side of the equation.
9e + 7e = -7e + 7e

Combine like terms: 9e + 7e = 16e
16e = -7e + 7e

Combine like terms: -7e + 7e = 0
16e = 0

Divide each side by '16'.
e = 0

Simplifying
e = 0

See similar equations:

| (2x+9)-5=0 | | 2+2x+2=14 | | -p^2-5p+16=0 | | 1/8z=7 | | X^2*ln(x)+1=0 | | .4x=20000 | | 36=x^5 | | J^2-12j-47=0 | | 5x-6y+2=0 | | .13z=7 | | 24x+50=x^2+24x-50 | | 3c+2=16+8c | | .166x=4 | | 100=18x+b+d | | 6n-34=-6h+14 | | (5x-10)(5x-5)=0 | | 15x^2-5x=4 | | 15-r=4r+2 | | 1/6×=4 | | 13y-2= | | 4k^2=16-k | | 4s+12=11s-16 | | 4g+16=-13 | | 3(3)-2(-2)= | | 4*7*2= | | (7x+4)-(x-9)=1 | | 2p+12=16 | | 2thirdsy=16 | | -6-2y= | | 3*-2+2y= | | 2x+2x=3x+3 | | Z=8-2i |

Equations solver categories